2012
DOI: 10.1371/journal.pone.0044049
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among Vascular-Tone Modulators Contribute to High Altitude Pulmonary Edema and Augmented Vasoreactivity in Highlanders

Abstract: BackgroundThe interactions among various biomarkers remained unexplored under the stressful environment of high-altitude. Present study evaluated interactions among biomarkers to study susceptibility for high altitude pulmonary edema (HAPE) in HAPE-patients (HAPE-p) and adaptation in highland natives (HLs); both in comparison to HAPE-free sojourners (HAPE-f).Methodology/Principal FindingsAll the subjects were recruited at 3500 m. We measured clinical parameters, biochemical levels in plasma and gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…Circulating ET-1 is elevated almost threefold at high altitude and to a greater degree in HAPE susceptibles and correlates with the rise in PA pressure [ 64 -66 ]. Other vascular mediators studied in over 400 subjects at 3,500 m with likely hypertensive effect on the pulmonary vasculature are greater in HAPE susceptibles, including plasma concentration of serotonin, 8-iso prostaglandin F, renin, and aldosterone [ 65 ].…”
Section: Neuro-humoral Responsesmentioning
confidence: 98%
See 2 more Smart Citations
“…Circulating ET-1 is elevated almost threefold at high altitude and to a greater degree in HAPE susceptibles and correlates with the rise in PA pressure [ 64 -66 ]. Other vascular mediators studied in over 400 subjects at 3,500 m with likely hypertensive effect on the pulmonary vasculature are greater in HAPE susceptibles, including plasma concentration of serotonin, 8-iso prostaglandin F, renin, and aldosterone [ 65 ].…”
Section: Neuro-humoral Responsesmentioning
confidence: 98%
“…While it is clear that altitude increases stable circulating markers of ROS production [ 80 , 81 ] and may play a role in AMS, it also appears that persons with higher HPV generate more ROS and less bioactive NO species across the lung [ 82 ]. In support of this, it was recently shown that HAPE-susceptible subjects have lower plasma concentrations of superoxide dismutase, an enzyme that converts oxygen radical (O 2 − ) to H 2 O 2 , a less potent oxidant species [ 65 ]. Isolated human PA endothelial cells exposed to 3 % oxygen produce more hydrogen peroxide and become more permeable to albumin, both of which are diminished in vitro and in vivo by antioxidants [ 83 ].…”
Section: Neuro-humoral Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 The ensuing oxidative stress primarily contributes to endothelial damage and vascular wall remodeling, which are potentially involved in the development of HA-related disorders in sojourners. 1,13 Thus, we can say that harsh climatic conditions at HA initiate a series of events in which there is an increased production of reactive intermediates, 29,30,32,33 vasoconstrictors such as endothelin 1 (ET-1), 32,34-36 5-hydroxytryptamine (5-HT), 8-iso-prostaglandin F2α (8-iso-PGF2α), 34 and various other proinflammatory cytokines. 29,35,[37][38][39] In contrast, there is a decrease in the production of vasodilators such as NO, 32,34,40,41 prostacyclins, 38 antioxidants, 29,30,38 and anti-inflammatory cytokines.…”
Section: Hypobaric Hypoxia-induced Oxidative Stressmentioning
confidence: 99%
“…The selection of genetic variants from such HA. 56 This may well be the case for the genes associated with the major physiological pathways that play crucial roles under the hypobaric hypoxic environment of HA, such as vascular homeostasis, 34,46 oxygen sensing, 57,58 and inflammatory pathways. 40,42,59,60 The genes that majorly associate with these pathways can easily be recognized as ET-1, 35 …”
Section: Notesmentioning
confidence: 99%